Epidemiology Study of Brucellosis in Polewali Mandar District, Indonesia - Fitri Amaliah; Bambang Sumiarto; Widagdo Sri Nugroho; Tri Untari; Dinar Hadi Wahyu Hartawan; Agustia Agustia (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2023)
This research aims to determine the prevalence rate of brucellosis in the Polman District, examine the risk factors associated with seropositive diagnoses of brucellosis, and also to determine the brucellosis case model at the farm level. This research was carried out through a cross-sectional study and obtained a sample size of 395 serum. Samples were tested through the RBT and CFT. Identification of risk factors is based on questionnaire data conducted on around 113 breeders spread across Polman Regency. The data were analyzed using univariate and bivariate descriptive statistics, chi-square, and odds ratio (OR). The brucellosis model at the farm level was analyzed by multivariate logistic regression. The results of this study indicate the prevalence of brucellosis in Polman Regency is 27.1%. Risk factors associated with diagnosis of brucellosis in Polman Regency included the history of abortion (p=0.000; OR=128), handling of aborted animal (p=0.000; OR=94.667), abortion at the end of pregnancy (p=0.000; OR=62.333), knowledge about brucellosis (p=0.000; OR=9.841), handling of residual abortions (p=0.003; OR=8,471), high grazing density (p=0.000; OR=6.861), introduction of new livestock (p=0.006; OR=5.833), dirty cage (p=0.003; OR=3.600), and grazing method (p=0.005; OR=3.167). Models of diagnosis brucellosis in Polman Regency is = -2,48923 + 3,38734 history of abortion + 2,06312 abortions at the end of pregnancy. The model shows that the history of abortion (β=+3.387; OR=29.588) and the incidence of abortion at the end of pregnancy (β=+2.205; OR = 7.871) can increase the seropositive diagnosis of brucellosis at the farm level.